Climate action through reducing food loss and waste: Lessons from Bangladesh, Malawi and Nepal - Srivastava, Nandita; Babu, Suresh Chandra; Anowar, Md Sadat (2024)
Reducing food loss and waste (FLW) is crucial to improving food security, reducing malnutrition, providing livelihoods for food system workers, and is key to combating climate change. Overall, food systems contribute an estimated 33 percent to anthropogenic greenhouse gas (GHG) emissions; food waste alone is responsible for eight to 10 percent. Yet, most countries that have submitted their Nationally Determined Contributions (NDCs) for reducing carbon emissions under the Paris Agreement have not included any commitments for reducing FLW. Many national FLW policies are not aligned with climate change goals and the NDCs. To make this bridge, countries must build supportive regulatory frameworks to reduce agrifood system emissions and include FLW as a mitigation measure.